Merchandising rules for shelf space allocation with horizontal and vertical positions - Czerniachowska, Kateryna (Zasady przydzielania miejsca w pionie i poziomie produktom na półkach sklepowych, 2021)
Retail visual merchandising techniques can maximize product attractiveness, create good store performance, attract more customers to the store, and as a result, they help to increase the retailer’s profit. These strategies make it easier for category managers to differentiate their products from other competitors. This study aimed to investigate the practical visual merchandising methods that influence customer preference of visiting a store and making purchases there. It provides interesting insights into the techniques of how retailers could deploy visual merchandising into the daily tasks to increase profit. The author proposed the framework and the shelf space allocation model, which includes visual merchandising constraints including store layout and traffic, aisles with regard to traffic direction; different shelf levels (special attention is given to the most profitable eye-level shelf); and shelf segments where convenience and local products should be placed. The results of the study could be a part of strategic category management in the retail business
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 1 (59), s. 9-33
Keywords: retailing; merchandising; store traffic; customer traffic flow; aisles; eye-level; sprzedaż detaliczna; ruch w sklepie; przepływ klientów; przejścia; poziom na wysokości wzroku